Experimental investigations of properties of plasma-dust formations in rf capacitive discharge - Dosbolayev, M.K.; Utegenov, A.U.; Ramazanov, T.S. (Recent Contributions to Physics, 2012)
In paper the results of investigation of properties of dust formation in RF discharges of argon-heliumand argon-hydrogen mixture were presented. In base of analysis of macroscopic properties of the system, such as pair correlation function and velocity distributions of dust particles, it was revealed that with addition of less argon to the system the structure of dust formation used to be in helium plasma noticeably changes.